Distribuição e perfil de susceptibilidade a antifúngicos de espécies de Candida isoladas de pacientes em Unidade de Terapia Intensiva e mãos de profissionais de saúde - Dalben, Yago Rodrigues (2023)
Candida is an opportunistic pathogen capable of triggering superficial and invasive infections, as well as causing outbreaks of nosocomial infections through horizontal transmission when strict hygiene protocols are not followed in hospital units. The aim of this study was to assess oral colonization by Candida spp. in patients admitted to an Intensive Care Unit between July 2021 and April 2022, as well as to conduct clinical, epidemiological, and microbiological characterization of patients who developed oral candidiasis and/or invasive candidiasis during this period. This study involved 209 patients who had their first oral swab sample collected within the first 24 hours of admission, followed by collections on days 2, 4, 6, and 8 after admission. Patients wearing upper complete dentures also had their dentures sampled. Swabs were inoculated onto CHROmagar™ Candida plates and incubated at 35°C for 72 hours. The total number of colony-forming units was quantified in case of growth. Abiotic surfaces, hands, and the retroauricular region of healthcare professionals were also sampled to assess Candida colonization. Samples were processed and inoculated onto Sabouraud dextrose agar. Recovered yeasts were initially identified using conventional methods, followed by identification using MALDI-TOF MS. Candida isolates of the same species recovered from patients, healthcare professionals, and abiotic surfaces were evaluated for genetic similarity using the AFLP method, as well as isolates recovered from patients' oral cavities who developed invasive candidiasis caused by the same species. Isolates subjected to AFLP analysis were also assessed for susceptibility to amphotericin B, anidulafungin, fluconazole, posaconazole, and voriconazole using the broth microdilution method. A total of 64.11% of patients showed Candida growth on at least one of the days during their hospital stay. Among them, 80.59% were colonized within the first 24 hours of admission. The remaining patients exhibited oral colonization on subsequent days: 50% on day 2, 26.92% on day 4, and 11.53% on days 6 and 8. Of the patients included in the study, 8.61% were diagnosed with oral candidiasis. The most frequent clinical manifestation was pseudomembranous candidiasis. Of the patients who were orally colonized, 2.23% developed invasive candidiasis. Out of 19 healthcare professionals evaluated, 89.47% were colonized by Candida. MALDI-TOF MS allowed for conclusive identification of isolates recovered from patients, with C. albicans (45.34%), C. tropicalis (15.7%), and C. parapsilosis sensu stricto (ss) (9.88%) being the most prevalent species. Twelve patients wore complete dentures, and 75% tested positive for Candida on swabs. Among the isolates recovered from healthcare professionals, eight species were identified, with C. parapsilosis ss being the most prevalent (56.52%). AFLP analysis showed that isolates of C. parapsilosis ss recovered from patients and healthcare professionals were highly correlated (≥97%). Three resistant C. albicans isolates were identified, including two isolates resistant to posaconazole (MIC=0.125 μg/mL) and one isolate resistant to fluconazole (MIC=16 μg/mL) and posaconazole (MIC=0.125 μg/mL). Patients admitted to the intensive care unit may exhibit increased colonization by Candida spp. from the second day of admission and may be colonized by various Candida species, with C. albicans being the most prevalent in our study. The high genetic correlation between C. parapsilosis ss isolates from different sites suggests that this pathogen is well adapted to this hospital unit, with the possibility of horizontal transmission through healthcare professionals. Furthermore, resistant C. albicans isolates to fluconazole and posaconazole were identified in the study.